Exploring the structural diversity and evolution of the D1 subunit of photosystem II using AlphaFold and Foldtree - Kim,TD; Pretorius,D; Murray,JW; Cardona,T (Physiologia Plantarum, 2025)
Although our knowledge of photosystem II has expanded to include time-resolved atomic details, the diversity of experimental structures of the enzyme remains limited. Recent advances in protein structure prediction with AlphaFold offer a promising approach to fill this gap in structural diversity in non-model systems. This study used AlphaFold to predict the structures of the D1 protein, the core subunit of photosystem II, across a broad range of photosynthetic organisms. The prediction produced high-confidence structures, and structural alignment analyses highlighted conserved regions across the different D1 groups, which were in line with high pLDDT scoring regions. In contrast, varying pLDDT in the DE loop and terminal regions appears to correlate with different degrees of structural flexibility or disorder. Subsequent structural phylogenetic analysis using Foldtree provided a tree that is in good agreement with previous sequence-based studies. Moreover, the phylogeny supports a parsimonious scenario in which far-red D1 and D1INT evolved from an ancestral form of G4 D1. This work demonstrates the potential of AlphaFold and Foldtree to study the molecular evolution of photosynthesis.